Neuroendocrine adaptations in renal disease - Feneberg, Reinhard; Schaefer, Franz; Veldhuis, Johannes D. (Pediatric nephrology, 2003)
Chronic renal failure (CRF) disrupts the time-dependent secretion of multiple hormones. The present review focuses on altered pulsatile release of peptide hormones. CRF is marked by impaired tissue actions, disorderly release patterns, and relative [growth hormone (GH)] or absolute [luteinizing hormone (LH)] deficiency of secretion. At the hypothalamo-pituitary level, experimental evidence suggests that CRF reduces the synthesis and/or release of the cognate hypothalamic releasing factors, GHRH and LHRH, and enforces excessive inhibition by somatostatin. Parathyroid hormone (PTH) and insulin are secreted in both basal and pulsatile modes, wherein the latter is putatively coordinated by autonomic innervation. Amplitude and frequency-dependent adaptations of PTH and insulin outflow fail in CRF, as assessed under steady-state conditions and during metabolic drive (i.e., calcium for PTH and glucose for insulin). A common feature in CRF is a diminished mass of hormone released per burst, due in principle to attenuation of feedforward signals and/or accentuation of (unknown) feedback signals. Damping of neuronal control and/or prolonged network response times may contribute to aberrant pulse frequency, disproportionate basal (nonpulsatile) hormone release, and consistent erosion of secretory process regularity in the uremic state. The homeostatic consequences of distorted secretory dynamics, tissue resistance, impaired hormone clearance, and altered mean agonist concentrations are evident in certain therapeutic interventions, such as GH supplementation in CRF.
Gesehen am 20.01.2021